Implementation of the Deep Learning Approach in 7th Grade Mathematics Learning At Al-Ikhlas Islamic SMP - Mukhlish Prihartono; Nur Annisah; Nurmaesih; Silvi Mardiana; Qonita Nurrohmah; Dessy Yani; Maria Dewati; Rosynanda Nur Fauziah (International Journal of Community Engagement Payungi, 2025)
This study was conducted to describe how the Deep Learning Approach (DLA) was implemented in seventh-grade mathematics instruction at Al-Ikhlas Islamic Junior High School, while also examining student responses, emerging challenges, and its effectiveness in improving conceptual understanding. The study used a qualitative approach with a case study design through in-depth interviews, classroom observations, and documentation. The results showed that teachers had implemented most of the DLA principles, including apperception, media use, contextual problem presentation, discussion, and providing reflection and feedback. Student engagement was highest in discussions (34%), followed by answering teacher questions (28%) and solving problems (24%), while questioning remained low (14%) due to a lack of confidence on the part of some students. Observations also showed that collaboration occurred but was not optimal due to the dominance of certain students, and some students remained passive. Overall, the implementation of DLA was proven to help increase student engagement, clarify concepts through real-life contexts, and reduce boredom, although obstacles such as math anxiety and low self-efficacy were still encountered. These findings confirm that DLA has the potential to improve the quality of mathematics learning if supported by the strengthening of collaborative strategies and ongoing mentoring.